(untitled) (Studia Prawnicze / The Legal Studies, 1971)
Autor artykułu przybliża czytelnikom regulacje prawa prywatnego międzynarodowego dotyczące uznawania udzielonych za granicą rozwodów i separacji. Przeprowadza wnikliwą analizę pojęć użytych w konwencji, przedstawia przesłanki jurysdykcji oraz opisuje proces legislacyjny, w wyniku którego powstała konwencja. Ponadto do artykułu załączona jest przetłumaczona na język polski treść konwencji. The author of this article familiarises readers with the private international law regulations on the recognition of divorce and separation obtained abroad. A thorough analysis of the concepts used in the Convention is conducted, the rationale for jurisdiction presented and the legislative process that resulted in the Convention are described. In addition, the content of the Convention, translated into Polish, is attached to the article.